Performance and digestibility of Nile tilapia fed with pineapple residue bran - 10.4025/actascianimsci.v34i1.12083 - Misleni Ricarte Lima; Maria do Carmo Mohaupt Marques Ludke; Mônica Calixto Ribeiro Holanda; Bárbara Wanderley Costa Pinto; Jorge Vitor Ludke; Elton Lima Santos (Acta Scientiarum. Animal Sciences, 2011)
Two experiments were conducted, the first being the digestibility of feed and the second performance in an attempt to evaluate the residue of pineapple bran in diets for Nile tilapia. Eighty animals weighing 63.9 ± 0.79 g in a completely randomized design were used to test the digestibility in order to evaluate the apparent digestibility of dry matter, crude protein, gross energy, digestible energy and digestible protein. In the performance of 240 juveniles were distributed in three ranges of weights: 34.9 ± 0.06, 44.4 ± 0.27 and 55.5 ± 0.10 g, in order to evaluate performance, yield Housing and somatic indices of Nile tilapia. The design was a randomized block with three blocks, with four treatments and five repetitions, rations in both experiments contained four levels of inclusion of pineapple bran residue (0, 5, 10 and 15%). The digestibility of the diets were: dry matter (76.17, 75.42, 75.31 and 75.77%), crude protein (87.90, 90.24, 89.51 and 89.03%) gross energy (79.12, 79.33, 79.07 and 77.48%), digestible energy (3649, 3559, 3560 and 3190 kcal kg-1) and digestible protein (29.28, 30.35, 29.82 and 29.79%), respectively. It was observed the significant effect on the carcass without head, so we recommend the inclusion of up to 10.39% for the inclusion of pineapple bran residue in diets of Nile tilapia